Translational Science and Evidence-Based Healthcare: A Clarification and Reconceptualization of How Knowledge Is Generated and Used in Healthcare - Alan Pearson; Zoe Jordan; Zachary Munn (Nursing Research and Practice)
The importance of basing health policy and health care practices on the best available international evidence (“evidence-based health care”) and on translating knowledge or evidence into action (“translation science” or “translational research”) is increasingly being emphasized across all health sectors inmost countries. Evidence-based healthcare is a process that identifies policy or clinical questions and addresses these questions by generating knowledge and evidence to effectively and appropriately deliver healthcare in ways that are effective, feasible, and meaningful to specific populations, cultures, and settings. This evidence is then appraised, synthesized, and transferred to service delivery settings and health professionals who then utilize it and evaluate its impact on health outcomes, health systems, and professional practice. Many of the common theories that address this translational process place it apart from the evidence-based practice cycle and most recognise only two translational gaps. This paper seeks to clarify the nature of evidence-based healthcare and translation science and proposes a reconceptualization that both brings together these two dominant ideas in modern healthcare and asserts the existence of a third fundamental gap that is rarely addressed the gap between knowledge need and discovery.